Non-native English Speaking Teachers’ Pragmatic Criteria in the Holistic and Analytic Rating of the Agreement Speech Act Productions of Iranian EFL Learners - Minoo Alemi; Mohammad Motamedi (Iranian Journal of Applied Language Studies, 2019)
Pragmatic rating is considered one of the novel and crucial aspects of second language education which has not been maneuvered upon in the literature. To address this gap, the current study aimed to inspect the matches and mismatches, to explore rating variations, and to assess the rater consistency between the holistic and analytic rating methods of the speech act of agreement in L2 by non-native English teachers. In this regard, 12 discourse completion tests (DCTs) for agreement accompanied by EFL learners’ responses to each situation were rated by 50 non-native English teachers. Initially, they were asked to rate it holistically, and the content analysis of raters’ comments revealed twelve agreement criteria. Grammatical structure was the prominent criterion which suggested that the raters were predominantly concerned with pragmalinguistics. In particular, the results of descriptive statistics demonstrated that there was a degree of divergence in the frequency of the criteria applied. Additionally, the teachers were asked to rate the pragmatic outputs analytically which showed that the raters were more consistent in the analytic phase. Finally, the findings indicated that there was a convergence between the two rating methods. The results of the present study implicated the necessity of rater training with regard to the rubric-based pragmatic rating. This study offers crucial pedagogical implications for syllabus designers, materials developers, language testers, and some suggestions for further research studies.